H2A Ubiquitination Alters H3-tail Dynamics on Linker-DNA to Enhance H3K27 Methylation. Issue 4 (28th February 2023) - Ohtomo, Hideaki; Ito, Shinsuke; McKenzie, Nicholas J.; Uckelmann, Michael; Wakamori, Masatoshi; Ehara, Haruhiko; Furukawa, Ayako; Tsunaka, Yasuo; Shibata, Marika; Sekine, Shun-ichi; Umehara, Takashi; Davidovich, Chen; et al.
Graphical abstract: Highlights: NMR characterizes the H3-tail dynamics by H2A ubiquitination and linker-DNA. H3-tail dynamically contacts DNA in the nucleosome with linker-DNA. H2A ubiquitination alters contacts between H3-tail and DNA. Linker-DNA and H2A ubiquitination facilitate H3K27 methylation. Abstract: Polycomb repressive complex 1 (PRC1) and PRC2 are responsible for epigenetic gene regulation. PRC1 ubiquitinates histone H2A (H2Aub), which subsequently promotes PRC2 to introduce the H3 lysine 27 tri-methyl (H3K27me3) repressive chromatin mark. Although this mechanism provides a link between the two key transcriptional repressors, PRC1 and PRC2, it is unknown how histone-tail dynamics contribute to this process. Here, we have examined the effect of H2A ubiquitination and linker-DNA on H3-tail dynamics and H3K27 methylation by PRC2. In naïve nucleosomes, the H3-tail dynamically contacts linker DNA in addition to core DNA, and the linker-DNA is as important for H3K27 methylation as H2A ubiquitination. H2A ubiquitination alters contacts between the H3-tail and DNA to improve the methyltransferase activity of the PRC2–AEBP2–JARID2 complex. Collectively, our data support a model in which H2A ubiquitination by PRC1 synergizes with linker-DNA to hold H3 histone tails poised for their methylation by PRC2–AEBP2–JARID2.